Hidden Treasures: Microbial Natural Product Biosynthesis off the Beaten Path - Friederike Biermann (American Society for Microbiology, 2021)
Microbes produce structurally diverse natural products to interact with their environment. Many of the biosynthetic products involved in this “metabolic small talk” have been exploited for the treatment of various diseases.